2021
DOI: 10.3390/ijerph182212254
|View full text |Cite
|
Sign up to set email alerts
|

The Continued Use of Social Commerce Platforms and Psychological Anxiety—The Roles of Influencers, Informational Incentives and FoMO

Abstract: Why does the continued use of social commerce platforms fail to promote consumer wellbeing? This study explores the roles of influencers, informational incentives and fear of missing out (FoMO) in the relationships between social commerce platform use and consumer mental health. Data were obtained through questionnaires, as well as constructing a research model. Statistical analysis and path analysis of the structural equation model were performed by the software IBM SPSS and AMOS, and the following results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 108 publications
1
2
0
Order By: Relevance
“…Browsing posts and media sharing were also identified as significant features that negatively impact mental health, with utility values of 45.03 and 25.40, respectively. These findings align with previous research that has identified the presence of influencers on social media as a potential source of stress and depression for regular users who may feel pressure to emulate these individuals [18]. Additionally, excessive exposure to social media videos has been linked to negative mental health outcomes [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Browsing posts and media sharing were also identified as significant features that negatively impact mental health, with utility values of 45.03 and 25.40, respectively. These findings align with previous research that has identified the presence of influencers on social media as a potential source of stress and depression for regular users who may feel pressure to emulate these individuals [18]. Additionally, excessive exposure to social media videos has been linked to negative mental health outcomes [20].…”
Section: Discussionsupporting
confidence: 88%
“…Young people may not understand this fact, and they are likely to think that something is wrong with themselves because they do not look as good as the posts made by their friends. The authors of [18] found that social media influencers significantly contribute to the poor mental health of social media users. Advertisements power most social networking platforms, and users have had to embrace the presence of ads alongside their digital social lives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of emotional experience, individuals under psychological anxiety may perceive fear, worry, nervousness, uneasiness, and annoyance, and may even have a sense of panic and imminent death. In terms of behavioral performance, individuals under psychological anxiety may experience fidgeting, facial tension, and sleepless nights ( Li et al, 2021 ; Wang and Zhang, 2021 ). Focusing on the aspect of English writing, the term psychological anxiety can be extended to writing anxiety or English writing psychological anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%